Innovation and Technology Based Digital Marketing Strategy in Increasing E-Commerce Business Sustainability - Azzah Wanajma, Elsa (Economic and Business Horizon, 2024)
The development of digital technology has driven major changes in the world of marketing, especially in e-commerce platforms. This study discusses various digital marketing strategies implemented by companies in increasing competitiveness and customer loyalty in the e-commerce environment. Using a literature study method, this study examines various marketing approaches such as discounts and promotions, loyalty programs, and the use of advertising targeting algorithms. In addition, this study also explores the role of technological innovations such as Artificial Intelligence (AI), Augmented Reality (AR), and Virtual Reality (VR) in improving customer experience and marketing effectiveness. The results of the study show that innovative and technology-based marketing strategies contribute significantly to increasing customer engagement and supporting business sustainability. In addition, sustainability and social responsibility factors are also increasingly becoming major concerns in digital marketing. With a deeper understanding of digital marketing strategies, companies can optimize the use of e-commerce platforms to achieve more sustainable business growth.